Easing the Discomforts of Pregnancy - Glenda L. Warren; Claudia Peñuela (EDIS)
Revised! FCS1068, a 3-page illustrated fact sheet by Glenda L. Warren and Claudia Peñuela, summarizes recommendations for several discomforts of pregnancy, including morning sickness, heartburn, constipation, swelling/fluid retention, fatigue, and dizziness. Includes references. Published by the UF Department of Family Youth and Community Sciences, May 2010.